(untitled) (Bangladesh Medical Journal Khulna, 2018)
Background: Meconium ileus is a common form of congenital intestinal obstruction. The condition results from the accumulation of sticky inspissated meconium in distal ileum. In about half the cases, however, the pathologic condition is complicated by volvulus, gangrene, perforation with meconium peritonitis. Relief of the obstruction is commonly accomplished with a variety of operative procedures. A number of operative procedures are in use, including Bishop-Koop enterostomy, Mikulicz ileostomy and primary closure Objective: Aim of this study was to evaluate the outcome of meconium ileus and its complications in two commonly practiced enterostomy procedure. Method: In this retrospective study from July 2007 to Jun 2017, a total of 52 cases of meconium ileus were included. Diagnosis of suspected cases was confirmed after laparotomy. Two commonly practiced ileostomy procedure were Mikulicz ileostomy and Bishop Koop ileostomy in this study. Survivors of all primary enterostomy underwent ileostomy closure after 3-6 months. Result: Mikulicz enterostomy was done in 38 cases and Bishop Koop ileostomy in 14 cases. After primary ileostomy 5 patients died following Mikulicz ileostomy and 2 after Bishop Koop ileostomy Among the 41 cases those who reached ileostomy closure, 35 were survived. Conclusion: Complications were more common after Mikulicz ileostomy and difficult to manage in our observation. Overall survival of meconium ileus was 66% in our study without any facilities of intensive neonatal care. Bang Med J (Khulna) 2017; 50 : 31-34